Laparoscopic hepatectomy for elderly patients: Major findings based on a systematic review and meta-analysis. Issue 30 (July 2018) - Chen, Ke; Pan, Yu; Maher, Hendi; Zhang, Bin; Zheng, Xue-yong
Abstract: Background: As the general population continues to age, there is an increase need for surgical management of elderly patients. Compared to open hepatectomy (OH), laparoscopic hepatectomy (LH) offers earlier mobilization, less blood loss, and shorter postoperative hospital stay. However, whether these advantages of LH over OH are retained in elderly patients remains to be clarified. Therefore, in this study, we sought to evaluate the feasibility, safety, and potential benefits of LH for elderly patients. Methods: A systematic search of PubMed, Embase, Cochrane Library, and Web of Science was performed to identify studies that compared LH and OH. Studies comparing LH in elderly and LH in nonelderly patients were also identified. Outcomes of interest included conversion rate, operative time, intraoperative estimated blood loss, length of hospital stay, rate and type of morbidity, mortality rate, margin status (R0), and long-term oncologic outcomes. Results: Nine studies met our inclusion criteria for this analysis. Of these, 5 compared LH and OH in elderly patients, 3 compared LH in elderly and nonelderly patients, and 1 included both outcomes. Compared to those with OH, elderly patients who underwent LH had similar operative times [weighted mean difference (WMD) = 1.15 minutes; 95% confidence interval (CI): −28.28–30.59, P  = .94], less intraoperative blood loss (WMD = −0.71 mL; 95% CI: −1.29 to −0.16, P  = .01), a lower rate of transfusion [risk ratio (RR) = 0.61, 95% CI: 0.40–0.94, P  = .02], comparable R0 rates (RR = 1.01; 95% CI: 0.96–1.07, P  = .70), less postoperative complications (RR = 0.61, 95% CI: 0.48–0.76, P  < .01), and shorter hospital stay (WMD = −3.22 days; 95% CI: −4.21 to −2.23, P  < .01). The limited long-term outcomes indicated that survival status was comparable between LH and OH for elderly patients. The pooled outcomes for elderly versus nonelderly patients indicated that the safety and effectiveness of LH over OH in elderly patients was not inferior to those in nonelderly patients. Conclusion: Our results indicate that LH is a feasible and safe alternative to OH in elderly patients, providing a lower rate of morbidity and favorable postoperative recovery and outcomes.